Leadership in an Organization from the Perspective of Leaders and Employees - Kopertyńska, Maria Wanda; Dernowska-Żaczyk, Natalia; Stefaniuk-Żygadło, Katarzyna (Przywództwo w organizacji z perspektywy liderów i pracowników, 2025)
Aim: The purpose of the research was to determine how leadership is perceived in the organization and what challenges leaders face. Methodology: The research method adopted was a diagnostic survey using a questionnaire. This survey was supported by a guided semi-structured interview. Results: The conducted research allowed to conclude that both leaders and employees recognised that the basis of leadership is a common interpretation of the situation and environment, as well as inspiring employees. In the opinion of leaders and employees, a leader builds authority mainly through respect for others and the ability to make decisions. The most important features of a leader should be orientation towards success, determination and decisiveness, self-confidence, openness, empathy change, supporting development and understanding business. In turn, diligence, justice and decisiveness are the main values that a leader should follow. Implications and recommendations: Future research should explore how leadership expectations vary across different generational cohorts. Originality/value: This research uniquely combines a broad-scale diagnostic survey with qualitative, semi-structured interviews, offering both quantitative robustness and rich contextual insights into leadership perception.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2025; vol. 69, nr 2, s. 80-89